The secret police dossier of Herta Müller : a "file story" of Cold War surveillance - Glajar, Valentina (Culture and power in German-speaking Europe, 1918-1989, 2023)
""Herta Müller should share her Nobel with the Securitate." This comment by a former officer in the Romanian secret police, or Securitate, was in reaction to hearing that Müller, a German writer originally from Romania, had won the 2009 Nobel Prize for Literature. Communist Romania's infamous secret police was indeed a protagonist in Müller's work, though an undesired and dreaded one: most of her writings are deeply and explicitly anchored in Ceaușescu's Romania and her own traumatic experiences with the Securitate. Müller's file traces her surveillance from 1983 until after she emigrated to West Germany in 1987. She has written extensively in reaction to reading her file, but primarily addresses its gaps, begging the question what information the file does in fact contain"--